2019
DOI: 10.3389/fpls.2019.00554
|View full text |Cite
|
Sign up to set email alerts
|

Field-Based High-Throughput Phenotyping for Maize Plant Using 3D LiDAR Point Cloud Generated With a “Phenomobile”

Abstract: With the rapid rising of global population, the demand for improving breeding techniques to greatly increase the worldwide crop production has become more and more urgent. Most researchers believe that the key to new breeding techniques lies in genetic improvement of crops, which leads to a large quantity of phenotyping spots. Unfortunately, current phenotyping solutions are not powerful enough to handle so many spots with satisfying speed and accuracy. As a result, high-throughput phenotyping is drawing more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 58 publications
0
58
0
Order By: Relevance
“…When equipped with digital cameras, UAVs can be used to estimate canopy surface and biomass (Liebisch et al, 2015) with multispectral cameras or hyperspectral sensors to characterize physiological processes such as chlorophyll fluorescence or nitrogen levels (Camino et al, 2018) or plant water status using thermal imaging (Gómez-Candón et al, 2016;Gonzalez-Dugo et al, 2015). For short crops, such as wheat, ground based phenotyping robot often termed "Phenomobile" have also been developed (Madec et al, 2017;Qiu et al, 2019). In addition to cameras similar to those on UAVs, they can carry heavy and energy-demanding sensors such as LiDAR and additional lights to be independent of natural sunlight varying in quality and quantity.…”
Section: High-throughput Phenotyping Of Cwr Resources For Research Anmentioning
confidence: 99%
“…When equipped with digital cameras, UAVs can be used to estimate canopy surface and biomass (Liebisch et al, 2015) with multispectral cameras or hyperspectral sensors to characterize physiological processes such as chlorophyll fluorescence or nitrogen levels (Camino et al, 2018) or plant water status using thermal imaging (Gómez-Candón et al, 2016;Gonzalez-Dugo et al, 2015). For short crops, such as wheat, ground based phenotyping robot often termed "Phenomobile" have also been developed (Madec et al, 2017;Qiu et al, 2019). In addition to cameras similar to those on UAVs, they can carry heavy and energy-demanding sensors such as LiDAR and additional lights to be independent of natural sunlight varying in quality and quantity.…”
Section: High-throughput Phenotyping Of Cwr Resources For Research Anmentioning
confidence: 99%
“…Though automated subcanopy phenotyping comes with some challenges, the potential for benefit to plant biology and plant breeding communities is immense and real. The capabilities of subcanopy rovers have been recognized by multiple groups (Mueller‐Sim et al, 2017; Kayacan et al, 2018; Stager et al, 2019), and the promise of lidar for in‐field characterization of plant architecture has also been recognized (Qiu et al, 2019; Su et al, 2019). By combining novel phenotyping and data analysis techniques, we have demonstrated that rover‐based phenotyping by lidar can produce LSPs that are heritable and contain information about plant architecture and plot‐level biomass distribution.…”
Section: Resultsmentioning
confidence: 99%
“…To be constructive to breeding programs, phenotyping methods must be robust, automated, sensitive, and amenable to plot sizes. The ability to get more rapid growth responses of genetically different plants in the eld and transmit these responses to individual genes, novel technologies such as proximal sensing, robotics, integrated computational algorithms and robust automated aerial image analytical frameworks are urgently needed [7].…”
Section: Introductionmentioning
confidence: 99%